Pembiayaan Murabahah pada Perbankan Syariah dalam Perspektif Hukum di Indonesia - Basri, Jainudin; Dewi, Anggraini Kusuma; Iswahyudi, Gesang (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2022)
Murabahah financing is one of the Islamic banking products. This financing is done by entering into an agreement between the bank and the customer. Murabahah is the sale and purchase of goods at the original price with an additional agreed profit. The characteristic of murabahah is that the seller must notify the buyer of the purchase price of the product by stating the amount of profit. Murabaha can be done in two ways, namely by purchasing orders and without orders. The implementation of murabahah financing has a legal basis that refers to the Al-Quran, Al-Hadith and fatwas from the National Sharia Council as well as several other regulations related to the business activities of Islamic banks as Financial Intermediaries, namely collecting and distributing funds to the public. This research is a type of normative legal research, which is aimed only at written regulations and or statutory regulations, as well as expert opinions. Sources of data used come from the library (liberary research), such as books, court decisions and others. Meanwhile, the analysis used in this study uses qualitative methods, which describe quality data in the form of regular, systematic, logical, non-overlapping sentences.